LEARNER AUTONOMY IN VOCABULARY LEARNING - A STUDY ON STUDENTS OF THE INTERNATIONAL STANDARD PROGRAM, VNU - Trần, Thị Ngân (2021)
Initially, the study aims at identifying ISP students‟ awareness of learner autonomy and vocabulary learning. By doing so, the researcher wishes to have an insight into students‟ use of materials and strategies in their process of autonomous vocabulary learning. Secondly, the researcher investigates the issue from the teachers‟ perspective, so as to figure out the techniques employed by teachers to foster students in their vocabulary learning and the effects of such techniques on the students. The data collected will serve as a basis to propose solutions for better use of teacher‟s instructions in fostering students‟ autonomy in learning vocabulary and accordingly benefits the future generations of the International Standard Program